TINGKAT KECEMASAN PASCA GEMPA BUMI WARGA DESA CIJENDIL KECAMATAN CUGENANG KABUPATEN CIANJUR JAWA BARAT - Caswati, Neng Cica; Sudharmono, Untung (STIKES Suaka Insan, 2023)
The occurrence of earthquakes has objectively been shown to be closely related to the onset of mental health problems such as depression, anxiety, and post-traumatic stress disorder after a disaster, which can have a negative impact if continuously felt by victims. The purpose of this study was to determine the level of anxiety after the earthquake of residents of Cijedil Village, Cugenang District, Cianjur Regency, West Java. The research method used was quantitative descriptive. Sampling was using accidental sampling technique, where 129 research subjects were victims after the earthquake in Cijedil Village, Cugenang District, Cianjur Regency, West Java Province. The instrument used in this study was the Hamilton Anxiety Rating Scale (HARS) questionnaire. This study showed the results of the majority of post-earthquake victims experiencing sleep disorders, namely as many as 68 respondents (52.71%). This study also showed that 72 respondents (55.81%) were in the mild anxiety category. It is recommended for post-earthquake victims to increase coping with stress management that effectively reduces anxiety levels, such as religious activities, cognitive behavior therapy, art therapy, healing therapy, emotional support, and play therapy. Keywords : Anxiety, Earthquake, Mental health